(untitled) (American Journal of Islam and Society, 1987)
Introduction Traditional banking is rejected by Islamic scholars mainly because of interest. Interest-bearing banking is supposedly being replaced by profit-sharing banking organized on the basis of two-tier mudambu. Seigniorage (difference between face value and intrinsic value of money) resulting from expansion in demand deposits will continue accruing to the interest-free banking system. Islamic economists consider it unjust to leave the seigniorage in the hands of private banks. Money experts feel strongly that the seigniorage should be transfered to society by financing welfare projects. A dual banking scheme is proposed here that will accomplish this task and contribute towards achievement of some other socio-economic goals of an Islamic society. The major role of banlung for an economy is presented in section I. Interestfree banlung is outlined in section II. Dual banlung scheme, with its justification and socio-economic implications, is proposed in the final section. I. General Role of Banking Economists classify all economic agents into households, business firms, and government. An economic dgent must operate within its budget constraint. The budget of an economic unit could be balanced, in deficit, or in surplus for a given period depending on, respectively, whether its income matches its expenditures, income exceeds its expenditures, or expenditures exceed its income. Savings from the surplus economic units (SEU) are transferred to the deficit economic units (DEU)in order to satisfy current investment and consumption needs of DEUs and increase incomes of SEUs for the ensuing ...